Effects of central and peripheral administration of leptin on pain threshold in rats and mice - Kutlu, S; Canpolat, S; Sandal, S; Ozcan, M; Sarsilmaz, M; Kelestimur, H (Maghira & Maas Publications, 2003)
OBJECTIVE: This study was planned to investigate the effects of exogenous leptin on the pain threshold. METHODS: Adult male Wistar rats weighing 250-300 g and mice weighing 25-30 g were used in this study Leptin was intracerebroventricularly (i. c. v.) injected in a dose of 3.5 mug/rat. Mice were intraperitoneally (i. p.) injected with leptin in a dose of 25 mug/mouse. Control animals were injected with the respective vehicle. The pain threshold test was performed using hot plate analgesia meter. The experiments were performed during the day and at night. The data were statistically analysed by Mann-Whitney U test. Level of significance was set at p<0.05. RESULTS: During the day, there were no significant changes in hot plate latencies half an hour after i.c.v. injection of vehicle or leptin in the control and leptin-treated rats, respectively At night, like during the day, i.c.v. injection of neither vehicle nor leptin caused any significant change in pain sensitivity. In mice, i.p. injection of leptin decreased latencies significantly (p<0.05) during the day and at night. Thus, leptin caused an increase in pain sensitivity during the day and at night. CONCLUSION: These results clearly demonstrated that leptin has a decreasing effect on pain threshold if it is peripherally administered in mice.
Keywords: leptin; pain threshold